The knowledge of prevention of mother to child transmission among pregnant women at Mabote clinic, Tsepong, Lesotho after voluntary counselling and testing - Olorunfemi, Adebola Folashade (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.